Socio-demographic and obstetric factors influencing choice of facility for delivery among pregnant women at Kasangati Health Center IV. A cross-sectional study. - Suzan Oyesigye; Doreen Agabamukama; Mrs. Grace Denise Akwang; Ms. Kamiat Nabibuga (SJ Gynecology and Obstetrics Africa, 2026)
Background: The study aimed at determining the socio-demographic and obstetric factors affecting choice of facility for delivery among pregnant women attending antenatal care at Kasangati Health Center IV, Wakiso District. Methodology: A descriptive cross-sectional design was used, and a questionnaire was used to collect data from 32 mothers attending antenatal care at Kasangati Health Center IV who were randomly selected. Collected data were analysed using descriptive statistics with the aid of SPSS 27, and results were presented in the form of frequencies and percentages using tables, graphs, and charts. Results: Findings show that most of the respondents, 17(42.5%), were between 26-35 years of age, and the least, 3(7.5%), were above 45 years of age. The majority of the participants, 19(47.5%), had a secondary education level, and 18 (45%) were running a small business as their occupation. Slightly above half of the participants, 21(52.5%), indicated that the distance from their home to the delivery health facility was more than 5km, suggesting long distances. The majority, 32(80%) of respondents, agreed that a history of adverse pregnancy outcomes pushes women towards facility-based deliveries, while 23(57.5%) indicated that their household income was between 500,000-1,000,000/=, whereas 24(60%) indicated that they had ever experienced malpresentation. This implies a fear of an increased risk of complications. Conclusion: While higher education, income, and previous obstetric complications positively drive the selection of a delivery center, physical distance remains a persistent negative barrier to care access. Recommendations: The administration of Kasangati Health Center IV should improve its delivery services to be competitive. Pregnant mothers residing more than 5km to delivery health facility choose a nearby clinic, which may not have good service, or delivery from home.